Strategic Awareness and Its Impact on Achieving Sustainable Competitive Advantage: An Exploratory Study at the Ministry of Culture, Tourism and Antiquities - Shakir Neamah Heriz Alalaaq; Akram Abdulrahman Abdulkareem (International Journal on Economics, Finance and Sustainable Development, 2026)
This research aims to highlight the concept of organizational awareness and its role in achieving sustainable competitive advantage through an exploratory study within the Ministry of Culture, Tourism, and Antiquities. The research stems from the following question: To what extent does organizational awareness, in its various dimensions, contribute to enhancing an organization's ability to achieve sustainable competitive advantage The research employed a descriptive-analytical approach. Data was collected using a questionnaire distributed to a sample of ministry employees to identify the prevailing level of organizational awareness and its impact on the dimensions of sustainable competitive advantage: quality, efficiency, innovation, and responsiveness. The research yielded several findings, most notably a significant positive correlation and influence between organizational awareness and achieving sustainable competitive advantage. This indicates that a high level of organizational awareness contributes to improved institutional performance and enhances an organization's ability to sustain itself and adapt to changes. The results also demonstrated the importance of fostering a culture of organizational awareness through leadership, training, and knowledge sharing. The research recommends adopting administrative policies that promote organizational awareness among employees, given its pivotal role in supporting sustainable competitive advantage and achieving the ministry's strategic objectives.